2018
DOI: 10.1590/1981-6723.16817
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters of tomatoes submitted to different doses of gamma radiation

Abstract: Ionizing radiation can be used for different purposes in the food industry. In this study, the effect of irradiation doses (0, 0.5, 1.0 and 1.5 kGy) on the quality parameters of long life tomatoes (Lycopersicon esculentum Mill.), was evaluated during 4 storage periods (1, 7, 14 and 21 days). The different treatments were evaluated by analysing for colour, pH, total soluble solids (TSS), total titratable acidity (TTA), ratio (TSS/TTA), hardness, total lycopene and ascorbic acid contents, weight loss and maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…These findings agree with the study on cherry tomatoes by Guerreiro et al (2016) who found no effect due to gamma irradiation at 1.3 kGy compared to untreated samples—color is strongly affected by fruit ripeness. Similar findings were reported by Desai and Joshi (2018), Loro et al (2018), and Munir et al (2018) at slightly higher doses. Since the values of all irradiated samples were not different ( p > .05) from those for the controls in our study, the applied doses did not induce changes in the color of tomatoes that could result in noticeable sensory quality degradation.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These findings agree with the study on cherry tomatoes by Guerreiro et al (2016) who found no effect due to gamma irradiation at 1.3 kGy compared to untreated samples—color is strongly affected by fruit ripeness. Similar findings were reported by Desai and Joshi (2018), Loro et al (2018), and Munir et al (2018) at slightly higher doses. Since the values of all irradiated samples were not different ( p > .05) from those for the controls in our study, the applied doses did not induce changes in the color of tomatoes that could result in noticeable sensory quality degradation.…”
Section: Resultssupporting
confidence: 90%
“…Firmness as the peak force from a compression test using a small cylindrical probe (2–4 mm diameter) is a common method to evaluate texture of tomatoes (Al‐Dairi et al, 2021; Guerreiro et al, 2016; Loro et al, 2018). Changes in firmness (texture) were evaluated using a TA‐CT3 Brookfield Texture Analyzer (Brookfield AMETEK, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiation of male insects might end in dominant deadly mutations within the spermatozoan, killing spermatogonia cells, inactivation of the spermatozoan, and weakening of the males. Reckoning on the dose and age or physiological state of the insect, irradiation of the actively growing stages of the Associate in Nursing insect will have many effects [7]. The majority of genetic sterility is caused by irradiation, which results in failure of spermatozoan bundles to separate, lack of motility within the spermatozoa, failure of the spermatozoan to maneuver through the spermatheca, or other malfunctions that may stop copying and can be induced in either sex by selecting the appropriate dose and biological process stage [8].…”
Section: Introductionmentioning
confidence: 99%